The Effectiveness of Using Matching Cards in Enhancing Students’ Interest in Learning Arabic - Salma, Mutiara Dwi; Baihaqi, M; Huda, Hisbullah; Rofiq, Ainur (Nurul Jadid University, 2025)
This study tested the effectiveness of matching cards in increasing interest in learning Arabic for eighth-grade students at MTsN 2 Surabaya. The background was that monotonous Arabic learning methods made students less interested. Using quantitative and quasi-experimental methods, this study used tests, observations, and questionnaires. The results showed a sharp increase in student interest and grades after using matching cards, as evidenced by a t-test with significant results (<0.05) and an average increase of 13.545 points. This indicates that interactive media such as matching cards are effective in making learning Arabic more varied, enjoyable, and increasing student motivation and achievement. The results of this study also provide practical implications for teachers in developing more creative and innovative learning strategies. Matching cards can be used as an alternative method for teaching vocabulary, which is often considered difficult and boring. Through game activities, students not only practice memorizing words but also engage in aspects of cooperation, communication, and social interaction in the classroom. Thus, the learning process not only focuses on cognitive aspects but also builds motivation, positive attitudes, and social skills. This study recommends the use of similar media in other subjects to create a fun and effective learning environment